Comparison of atmospheric microplasma and plasma jet irradiation for increasing of skin permeability. (19th July 2016) - Shimizu, K; Tran, N A; Hayashida, K; Blajan, M
Abstract: Atmospheric plasma is attracting interest for medical applications such as sterilization, treatment of cancer cells and blood coagulation. Application of atmospheric plasma in dermatology has potential as a novel tool for wound healing, skin rejuvenation and treatment of wrinkles. In this study, we investigated the enhancement of percutaneous absorption of dye as alternative agents of transdermal drugs. Hypodermic needles are often the only way to deliver large-molecule drugs into the dermis, although a safe transdermal drug delivery method that does not require needles would be desirable. We therefore explored the feasibility of using atmospheric microplasma irradiation to enhance percutaneous absorption of drugs, as an alternative delivery method to conventional hypodermic needles. Pig skin was used as a biological sample, exposed to atmospheric microplasma, and analyzed by attenuated total reflection-Fourier transform infrared spectroscopy. A tape stripping test, a representative method for evaluating skin barrier performance, was also conducted for comparison. Transepidermal water loss (TEWL) was measured and compared with and without atmospheric microplasma irradiation, to quantify water evaporation from the inner body through the skin barrier. The results show that the stratum corneum, the outermost skin layer, could be chemically and physically modified by atmospheric microplasma irradiation. Physical damage to the skin by microplasma irradiation and an atmospheric plasma jet was also assessed by observing the skin surface. The results suggest that atmospheric microplasma has the potential to enhance percutaneous absorption.